Dancing in the Streets: Political Action and Resistance in Melbourne. Issue 2 (2nd April 2016) - Bird, Susan
ABSTRACT: Music and dance can be viewed as modes of resistance to state power. Local laws in Melbourne, such as the Activities Local Law 2009, prohibit behavior in public spaces that cause a "nuisance"—a term that, according to the regulation, is defined by its "ordinary common meaning." Thus unauthorized dancing in public spaces, and the music that accompanies it, is often restricted as forms of public "nuisance." Such restrictions seem geared toward controlling aspects of the city that do not fit a commercial purpose. Occupying space with unauthorized dance and music offers the opportunity to create a temporary space of resistance and provides room for the inclusion of minority groups on city streets. Auto-ethnographic accounts of involvement in underground dance parties and "Reclaim the Streets" protests are used in exploring these ideas, which are underpinned by an engagement with the work of Henri Lefebvre and Michel de Certeau, both of whom argue the case for a more open and accepting city.